Strategi Desain Bangunan Hospitality yang Mampu Beradaptasi di Masa Pandemi - I Gusti Agung Putri Tratayani; I Kadek Yadnya Saputra; Ida Ayu Pradnyaparamita; Ni Komang Indra Mahayani; I Nyoman Warnata (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2021)
The Covid-19 pandemic has hit the world, and Indonesia is also one of them. This pandemic is caused by a virus of the Coronavirus group, namely SARS-CoV-2 or often called Covid-19. This virus can infect the respiratory system, ranging from mild flu to death. The spread of this virus is classified as very fast because through the mouth when coughing or sneezing, this virus can also be transmitted through direct contact with infected people. Therefore, this virus spreads quickly in crowded places. To prevent the rapid spread of the virus, the government is carrying out a program in which people's activities are outside their homes. This restriction is done to reduce activities that can cause crowds. The government also recommends that people reduce the use of air conditioning, optimize natural ventilation and increase the use of sunlight, this can reduce the spread of the virus. Therefore, this study aims to implement strategies that can prevent the spread of Covid-19 in buildings. The COVID-19 pandemic has hit the world, and Indonesia is also included in it. This pandemic is caused by a virus of the Coronavirus group, namely SARS-CoV-2 or often called Covid-19. This virus can infect the respiratory system, ranging from mild flu to death. The spread of this virus is classified as very fast because through the mouth when coughing or sneezing, this virus can also be transmitted through direct contact with infected people. Therefore, this virus spreads quickly in crowded places. To prevent the rapid spread of the virus, the government is carrying out a program in which people's activities are outside their homes. This restriction is done to reduce activities that can cause crowds. The government also recommends that people reduce the use of air conditioning, optimize natural ventilation and increase the use of sunlight, this can reduce the spread of the virus. Therefore, this study aims to implement strategies that can prevent the spread of Covid-19 in buildings